Going the distance: A lesson study on deriving the distance formula - Chua, Von Christopher Gulpric (Animo Repository, 2019)
Purpose: The purpose of this paper is to determine the challenges that Filipino Mathematics teachers face while developing students’ ability to derive the distance formula; allow teachers to collaboratively formulate a lesson designed to address the challenges they have identified from their own practice; and determine how successful the lesson was and how it can be improved so that other teachers dealing with similar difficulties may be able to implement it. The teacher-participants employed Lesson Study (LS) as an approach to improving pedagogical practice. Data were based on the pre- and post-lesson discussions and individual reflection papers of the teacher participants. Design/methodology/approach: An action research methodology through LS approach was employed by the teacher participants. Data were based on the pre- and post-lesson discussions and individual reflection papers of the teacher participants. Findings: Based on the post-lesson discussion, the teachers agreed that the process of creating a lesson that seeks to develop the students’ ability to derive formulas are crucial to building understanding of the underlying mathematical concept. Also, teachers’ participation in LS was found to have been insightful as it developed in them a greater appreciation towards establishing a professional learning community that is directed towards examining problems that concerns majority of the teachers involved. Originality/value: Research in Philippine education has recently seen the increasing interest in LS as a potent pedagogical practice. Nonetheless, papers that report on LS practice in the local context remains to be lacking. This study contributes to the development of this research area and raises the need for Filipino Mathematics teachers to engage in both LS and action research to generate knowledge from their experiences. © 2019, Emerald Publishing Limited.